2019
DOI: 10.1002/hrdq.21346
|View full text |Cite
|
Sign up to set email alerts
|

Leadership behavior: A partial test of the employee work passion model

Abstract: This study examined empirical associations between employee cognitive perceptions of leader behavior (directive behavior, supportive behavior) and leader values (self‐concern, other orientation), employee positive affect and negative affect, and employee work intentions indicative of (dis)passionate employees. An internet‐based self‐report questionnaire survey was administered to 409 employees within three private sector organizations in Australia. Structural equation modeling indicated that supportive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 142 publications
2
28
1
Order By: Relevance
“…Furthermore, several EWPA model studies mentioned above (Egan et al, 2019;Roberts & Zigarmi, 2014;Zigarmi et al, 2011Zigarmi et al, , 2015Zigarmi & Roberts, 2012) have examined positive and negative affect to uncover notable differences in relationships between type of affectivity and the five intentions in the EWPA model. For example, Egan et al (2019) found strong positive correlations with positive affect and work intentions (rs ranged from .66 to .55). These findings were duplicated by Zigarmi et al (2015), which uncovered positive relationships between harmonious passion and work intentions (rs ranged from .38 to .49).…”
Section: Harmonious Passion Obsessive Passion and Work Intentionsmentioning
confidence: 99%
“…Furthermore, several EWPA model studies mentioned above (Egan et al, 2019;Roberts & Zigarmi, 2014;Zigarmi et al, 2011Zigarmi et al, , 2015Zigarmi & Roberts, 2012) have examined positive and negative affect to uncover notable differences in relationships between type of affectivity and the five intentions in the EWPA model. For example, Egan et al (2019) found strong positive correlations with positive affect and work intentions (rs ranged from .66 to .55). These findings were duplicated by Zigarmi et al (2015), which uncovered positive relationships between harmonious passion and work intentions (rs ranged from .38 to .49).…”
Section: Harmonious Passion Obsessive Passion and Work Intentionsmentioning
confidence: 99%
“…All four dimensions of authoritarian leadership reflect strict hierarchical relationships, high power distance, and low emotional communication between leaders and employees, which would have an impact on employees' subjective perceptions psychological feelings and subsequently on their work behaviors, including safety behavior ( 46 , 47 ). And we can explain it in terms of social exchange theory.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The cultivation of passion at work is considered to be the cornerstone of talent development. Many researches are conducted to check the intrapersonal effects of passion, such as burnout, mental illness, cognitive outcomes, and motivational factors (Bouffard, 2017;Carbonneau et al, 2010;Egan et al, 2019;. However, the purpose of the current study is to explore the antecedents of passion (Egan et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Passion is defined as strong feelings for work or activity which an individual likes, feels essential, and invests his energy and time in this activity or task (Vallerand et al, 2003(Vallerand et al, , 2010. Over many years, research studies on workplace passion have been growing and receiving remarkable prominence in both academic and business press Boonsathorn & Sirakiatsakul, 2018;Egan et al, 2019;Hatfield et al, 2012;Mageau et al, 2009;Newman et al, 2019;Pollack et al, 2020). The cultivation of passion at work is considered to be the cornerstone of talent development.…”
Section: Introductionmentioning
confidence: 99%